SMARTphone-based, early cardiac REHABilitation in patients with acute coronary syndromes: a randomized controlled trial. Issue 5 (27th August 2020) - Yudi, Matias B.; Clark, David J.; Tsang, David; Jelinek, Michael; Kalten, Katie; Joshi, Subodh B.; Phan, Khoa; Ramchand, Jay; Nasis, Arthur; Amerena, John; Koshy, Anoop N.; Murphy, Alexandra C.; et al.
Abstract : Background: There are well-documented treatment gaps in secondary prevention of coronary heart disease with a lack of clearly defined strategies to assist early physical activity after acute coronary syndromes (ACS). Smartphone technology may provide an innovative platform to close these gaps. Objectives: The primary goal of this study was to assess whether a smartphone-based, early cardiac rehabilitation program improved exercise capacity in patients with ACS. Methods: A total of 206 patients with ACS across six tertiary Australian hospitals were included in this randomized controlled trial. Participants were randomized to usual care (UC; including referral to traditional cardiac rehabilitation), with or without an adjunctive smartphone-based cardiac rehabilitation program (S-CRP) upon hospital discharge. The primary endpoint was change in exercise capacity, measured by the change in 6-minute walk test distance at 8 weeks when compared to baseline, between groups. Secondary endpoints included uptake and adherence to cardiac rehabilitation, changes in cardiac risk factors, psychological well-being and quality of life status. Results: Of the 168 patients with complete follow-up (age 56 ± 10 years; 16% females), 83 were in the S-CRP. At 8-week follow-up, the S-CRP group had a clinically significant improvement in 6-minute walk test distance (Δ117 ± 76 vs. Δ91 ± 110 m; P = 0.02). Patients in the S-CRP were more likely to participate (87% vs. 51%, P < 0.001) and adhere (72% vs. 22%, P < 0.001) to a cardiac rehabilitation program. Compared to UC, patients receiving S-CRP had similar smoking cessation rates, LDL-cholesterol levels, blood pressure reduction, depression, anxiety and quality of life measures (all P = NS). Conclusion: In patients with ACS, a S-CRP, as an adjunct to UC improved exercise capacity at 8 weeks in addition to participation and adherence to cardiac rehabilitation (Australian New Zealand Clinical Trials Registry; ACTRN12616000426482).